Історія крізь призму духовності: візія Романа Іваничука - Ільницький, М.М. (Слово і Час, 2019)
У статті розглянуто історичні романи Р. Іваничука “Мальви”, “Черлене вино”, “Шрами на скалі” та “Четвертий вимір” під кутом зору відображених у них духовних запитів епохи. Увага зосереджена на художній трансформації суспільно-філософських ідей різних періодів історії України та їх перегуків із сучасними проблемами. The paper deals with the historic novels written by Ukrainian writer Roman Ivanychuk in 1960s – 1980s. The emphasis is given to the peculiarities that distinguish his works among the similar novels on the Ukrainian history written at the same period. The researcher sees the main diff erence in the fact that R.Ivanychuk focused not so much on the heroic acts of his characters as on their characteristics of representatives of the epoch. He paid the most attention to the spiritual awakening of the nation being under pressure of the forced assimilation and in danger of extinction. These features of the historic novels by this writer were already noticeable in his first novel “Malvy” (“Mallows”, 1968). The work focused on the problem of “janissaries”, especially relevant at that time. It was interpreted as the loss of historical memory and national identity on the one hand, and the inevitable end of the empire that exploits enslaved neighbors on the other. The aesthetic symbolism is realized in the image of a luxuriant plane tree which is drained by mistletoe, with the fatal end of a tree. The symbolism of this image is related to the idea of the Arabic philosopher of the 16th cent. Ibn Khaldun who stated that decline of an empire is caused by the loss of its vital sources. The novels “Cherlene vyno” (“Red Wine”, 1977) and “The Manuscript from Ruska Street” (1979) contain the aesthetic models that sound in tune with the scholarly ideas of contemporary historians (O. Apanovych, Y. Isaievych, M. Braichesvkyi). In particular it was the interest to the development of the education system and research studies, emergence of Brotherhood schools and book printing. Historic novels by R.Ivanychuk emphasize the conflict between the Artist and the system of ruling power (“Shramy na Skali”/“Scars on Rock”, 1982), where one can see allusions to the movement of the Sixtiers. The writer raised the problem of the moral choice between strict loyalty to the principles and the compromise. Then he explored the limits of justifying the compromise.